2018
DOI: 10.1039/c8sc02409j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded perylene bisimide J-aggregate aqua material

Abstract: A water-soluble perylene bisimide dye self-assembles in aqueous media into thermoresponsive aqua materials with photoluminescence within the biological transparency window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 65 publications
1
57
0
Order By: Relevance
“…In H 2 O, the absorption spectrum of [2PBI] ‐ 1 shows a slight redshift of 15 nm when compared to the spectrum in CHCl 3 and a considerable decrease in intensity of about 20 %, which are known trends for PBIs in aqueous environment . In H 2 O, cyclophane [2PBI] ‐ 1 is virtually non‐fluorescent (<0.1 %).…”
Section: Figurementioning
confidence: 99%
“…In H 2 O, the absorption spectrum of [2PBI] ‐ 1 shows a slight redshift of 15 nm when compared to the spectrum in CHCl 3 and a considerable decrease in intensity of about 20 %, which are known trends for PBIs in aqueous environment . In H 2 O, cyclophane [2PBI] ‐ 1 is virtually non‐fluorescent (<0.1 %).…”
Section: Figurementioning
confidence: 99%
“…In our previous work, we applied the concept of hydrogen bond directed self‐assembly to the class of at bay area fourfold phenoxy‐substituted PBIs ( Figure ). By this, well‐defined J‐aggregates could be achieved with stacking motifs from double‐ up to sextuple‐stranded helices in solution, [ 27,28 ] in gels, [ 29,30 ] and in the liquid‐crystalline state. [ 31–33 ] In‐depth photophysical studies for these J‐aggregates revealed highly desired properties including outstanding fluorescence quantum yields up to 90%, strong exciton coupling, and exciton migration for distances up to 100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The alkyl-chain functionalised PBIs can form organogels [13][14][15][16] upon lowering the solution temperature or increasing the PBI concentration. PBIs functionalised with oligo(ethylene glycol) groups can form hydrogels upon mixing with water 17,18 and PBIs functionalised with ionisable groups can form hydrogels [2][3][4][5][6]12,[19][20][21][22] upon neutralisation of the charge. Both organic and water-soluble functionalised PBIs have also reported to be able to form columnar liquid crystalline systems.…”
Section: Introductionmentioning
confidence: 99%